2021
DOI: 10.46445/ejti.v5i2.336
|View full text |Cite
|
Sign up to set email alerts
|

The Priority of the Church’s Ministry during a Pandemic

Abstract: The global COVID-19 pandemic has caused churches to change their worship patterns from meeting at church buildings to virtual worship at home to prevent transmission of the virus and comply with the health protocols set by the local governments. This study aims to determine the priority of the pastoral ministry during the COVID-19 pandemic and explore new strategies to be adopted analyze and examine the functions of the church, especially with regards to how the church responds previously during the pandemic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Regardless of the opportunities and challenges present, the COVID-19 pandemic becomes an encouragement to the Church to subscribe to the current development. Looking forward, the Church as an organization is expected to continue utilizing digital media as post-pandemic ministry media (Sastrohartoyo, Abraham, Haans, & Chandra, 2021). At first, it was apparent that COVID-19 negatively impacted the ministry of many church organizations.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the opportunities and challenges present, the COVID-19 pandemic becomes an encouragement to the Church to subscribe to the current development. Looking forward, the Church as an organization is expected to continue utilizing digital media as post-pandemic ministry media (Sastrohartoyo, Abraham, Haans, & Chandra, 2021). At first, it was apparent that COVID-19 negatively impacted the ministry of many church organizations.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, it was found that the church organisation formed virtual cell groups to facilitate discipleship to its members. Sastrohartoyo et al (2021) opined that one of the Church's priorities in doing its responsibilities is the maximisation of digital media in its activities, such as missionary work, teaching and discipleship. Then, research by Ekoliesanto, Santoso and Claudia (2022) shows that church digital ministry had a positive impact on the spiritual growth of youths.…”
Section: Introductionmentioning
confidence: 99%
“…The Digital Era is a rapidly emerging period. Digital media has made it easy to access information from anywhere in the world (Allan & Allan, 2020;Saptorini et al, 2022;Sastrohartoyo et al, 2021). Indeed, this facilitates people's access to information and knowledge services.…”
Section: Introductionmentioning
confidence: 99%